Alētheia in Gorgias of Leontini. An Excerpt from the History of Truth - Leeten, Lars (Peitho. Examina Antiqua, 2022)
It is often assumed that the concept of alētheia, or ‘truth’, in Gorgias of Leontini belongs to the art of rhetoric. Along these lines, it is usually understood as an aesthetic concept or even a mere ‘adornment’ of speech. In this paper, it is argued, by contrast, that Gorgianic alētheia is a definable criterion of speech figuring in the practice of moral education. While the ‘truth’ of a logos indeed has to be assessed on aesthetic grounds, the underlying concept of alētheia is predominantly ethical. For Gorgias, speech is ‘true’ when it promotes virtue (aretē) by being expressive of virtue. The principle stated in the opening passage of the Encomium of Helen, that a speaker has ‘to praise what is praiseworthy and to blame what is blameworthy’, explains precisely this understanding of alētheia.